Measuring Knowledge Translation Uptake Using Citation Metrics: A Case Study of a Pan-Canadian Network of Pharmacoepidemiology Researchers. Issue 3 (2nd July 2016) - Rothfus, Melissa; Sketris, Ingrid S.; Traynor, Robyn; Helwig, Melissa; Stewart, Samuel A.
ABSTRACT: Collecting citation metric data is important, as research funders are increasingly demanding impact assessment, but there is limited consensus on the most rigorous and accurate approach. We compared three sources of citation counts (Google Scholar, Web of Science, Scopus) to determine their reliability, comprehensiveness, and currency. We identified each tool's strengths and limitations, particularly when considering team outputs. Citation counts varied, with poor overall agreement: Fleiss' kappa, 0.075 (95% CI [0.01, 0.12]). Researchers, funders, and administrators need to understand each tool's unique strengths and limitations and develop guidelines for use within specific contexts.